A proteção jurídica de adolescentes em face da propagação de discurso de ódio neonazista em mídias cruzadas: estudo micro comparado entre Brasil e Alemanha - Sassi, Ana Carolina (2025)
This research addresses the normative protection of adolescents in the face of the use of crossmedia strategies on the TikTok and Telegram platforms, which are employed as tools for disseminating neo-Nazi content. The study proposes a comparative analysis of the measures adopted in Germany and Brazil. While neo-Nazi hate speech, until recently, did not seem to generate significant concern among Brazilian authorities, in Germany, due to its historical background, it is a highly sensitive issue that has been regulated by specific norms for many years, focusing on the prevention and punishment of those responsible for its propagation. Given the rise of such discourse in Brazil and the consequent concern about adolescent development, this study questions to what extent the country adopts actions similar to those of Germany and whether it has effective legal mechanisms to protect adolescents from crossmedia strategies used to spread extremist ideologies on these digital platforms. Based on a hypothetical-deductive approach, the research investigates the legal protection of adolescents against the use of these strategies for disseminating neo-Nazi content, with an emphasis on the TikTok and Telegram platforms, from a comparative perspective between Brazil and Germany. The comparative study method was employed to analyze the similarities and differences between the Brazilian and German legal frameworks regarding the regulation and combat of cross-media strategies used by extremist groups. Additionally, bibliographic research and the technique of direct, systematic, and non-participant observation were used to examine the dissemination of such discourse on these respective social networks. The results highlight the plurality of meanings that digital platforms attribute to the narratives disseminated in the virtual environment, as well as the diversity of strategies adopted by extremist groups to spread neo- Nazi content, often circumventing the parameters established by state surveillance. In light of this scenario, it becomes evident that protecting adolescents in digital environments requires the continuous improvement of regulations and oversight mechanisms. The comparative analysis between Brazil and Germany shows that while the European country already has a consolidated legal structure to curb neo-Nazi hate speech, Brazil still faces challenges in implementing effective measures. The dissemination of content through cross-media strategies increases teenagers' vulnerability, exposing them to extremist discourse without adequate defense mechanisms. Given this, a more robust regulatory framework and public policies aimed at their protection have become urgent. In addition to state regulation, it is essential for digital platforms to take greater responsibility in identifying and removing harmful content. Social awareness and the strengthening of digital education are also fundamental in creating a safer environment, preventing teenagers' exposure and recruitment by extremist groups that exploit gaps in the regulation and oversight of digital spaces.